HUBUNGAN LINGKAR PINGGANG DENGAN KEJADIAN OSTEOPOROSIS PADA WANITA LANSIA - Donna Adriani; Salma Dhiya Wahid (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2022)
BACKGROUND In elderly women, there is estrogen reduction which causes parathyroid depression and results in decreased absorption of vitamin D and experiences the aging process. This leads to increased susceptibility to one of the metabolic diseases, osteoporosis. One of the risk factors for osteoporosis is nutritional status which can be assessed through bmi and waist circumference. This study determines the relationship between waist circumference and the incidence of osteoporosis in elderly women. METHOD The study used an observational study with a cross-sectional design that included 86 elderly women in November-December 2021 at the Puskesmas Mampang, South Jakarta. Sampling used nonrandom sampling method with consecutive sampling technique. Data were collected by interview using the FRAX® tool questionnaire for osteoporosis and measuring waist circumference with a measuring tape. Data were analyzed by chi-square statistical test with a significance value of p<0.05. RESULTS The most age group experiencing osteoporosis is at the age of 71-90 years as many as 15 respondents 78.9%. There was a significant relationship between age and osteoporosis in elderly women (p-value = 0.028). Respondents who had osteoporosis with a waist circumference of <80 cm had (64.7%) more than those with a waist circumference of >80 cm. There was no significant relationship between waist circumference and osteoporosis in elderly women (p = 0.242). CONCLUSION There is a significant relationship between age and osteoporosis in elderly women and there is no relationship between waist circumference and osteoporosis in elderly women